Fossil energy consumption, economic development, inward FDI impact on CO2 emissions in Pakistan: Testing EKC hypothesis through ARDL model. (17th August 2020) - Ali, Muhammad Uzair; Gong, Zhimin; Ali, Muhammad Ubaid; Wu, Xiong; Yao, Chen
Abstract: The rapid rise in carbon production has been broadly accepted as a serious global issue and has become the centre of focus for policy makers and researchers. The consumption of fossil energy has been a chief source of carbon dioxide emission; in the meantime, academics focus on fossil energy consumption impact on carbon dioxide in developing like Pakistan is very infrequent. The current study investigated the long‐run and short‐run elasticities between economic development, square of economic development, fossil energy consumption, inward foreign direct investment (FDI) and carbon dioxide emission by utilizing the auto‐regressive distributive lag (ARDL) bound test technique for Pakistan from 1975 to 2014. The outcomes of co‐integration have confirmed the existence of long‐run relationship between variables. The results of short‐run and long‐run dynamics have confirmed the inverted U‐shaped relationship between economic development and carbon dioxide emission. ARDL model long run and short run coefficients have indicated that the fossil energy consumption has positive impact on carbon dioxide emission. Moreover, the impact of FDI on carbon emission is also quite considerable. Overall, the outcomes propose that Pakistan should encourage sustainable growth through energy efficiency, support the use of low GHG emission and efficient technologies, increase the consumption of renewable energy sources and channel the inward FDI to environment‐friendly technologies.